PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI IN HOUSE TRAINING (IHT) DI SMAN 1 KINALI - Suhelpi Suhelpi (JURNAL MANAJEMEN PENDIDIKAN, 2020)
Based on observations and supervision conducted by the author, it shows that the teacher's pedagogical competence in preparing lesson plans is still low. The purpose of this study was to describe and obtain information about Improving Teacher's pedagogical competence in Developing Learning Implementation Plans (RPP) Through In House Training (IHT) at Kinali 1 High School. This research is a school action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 4 productive teachers who taught at SMAN 1 Kinali. Research data were collected using observation sheets. Data were analyzed using percentages. The results showed that the implementation of In House Training (IHT) can improve the teacher's pedagogical competence in preparing lesson plans. This is evidenced by the initial average score of teacher competence before the program is 74. Then after IHT activities there was an increase in cycle I was 78.70 (good) and after that it increased in cycle II to 87.56 (very good).